A preparation process of magnesia-alumina spinel brick batching with improved anti-peeling performance

CN122916618APending Publication Date: 2026-10-16HAIWEI ZHONGXING HIGH-GRADE MAGNESIA BRICK CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611239109.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-16
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但这些方法在实际应用中仍面临增韧相分布不均、骨料与基质界面结合薄弱等难题,导致砖体在热循环中优先沿界面处开裂,抗剥落效果有限

Benefits of technology

本发明,通过采用含纳米二氧化锆分散液的改性硅溶胶对骨料进行真空超声辅助预包覆,在骨料表面形成了结合牢固的功能性涂层。该涂层在烧成过程中与基质组分原位反应生成含锆酸镁晶种的过渡界面层,有效增强了骨料与基质的结合强度,同时起到热应力缓冲作用,从根源上抑制了界面裂纹的萌生与扩展。同时微波干燥方式使砖坯内外受热均匀、水分梯度小,消除了传统热风干燥易产生的干燥开裂缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916618A_ABST
    Figure CN122916618A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of refractory material preparation, in particular to a magnesia-alumina spinel brick batching preparation process capable of improving anti-peeling performance, which comprises the following steps: S1, mixing fused magnesia particles and magnesia-rich spinel particles, and adding modified silica sol to obtain pre-coated aggregates; S2, mixing alumina micropowder, monoclinic zirconia micropowder and light-burned magnesium powder to obtain a composite binder powder; S3, dry mixing the pre-coated aggregates and the composite binder powder; S4, adding a temporary binder aqueous solution to the premixed material to mix and knead to obtain a mud; S5, pressing and forming the mud to obtain a green brick; and S6, microwave drying the green brick to obtain a dry green brick. According to the application, the modified silica sol containing nano zirconium dioxide is used to pre-coat the aggregates in a vacuum ultrasonic manner, a microwave drying process and in-situ generation of a toughening phase are combined, a transition layer containing magnesium zirconate is constructed on the aggregate-matrix interface, and a dispersion microcrack toughening structure is introduced, so that the interface crack propagation is inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of refractory material preparation technology, and in particular to a process for preparing magnesium aluminate spinel bricks with improved spalling resistance. Background Technology

[0002] Magnesium aluminum spinel bricks are widely used in thermal equipment such as the firing zone, transition zone, and ladle lining of cement rotary kilns due to their excellent high-temperature strength, resistance to alkali corrosion, and chemical stability. However, under frequent kiln shutdowns for maintenance and temperature fluctuations, cracks in the brick body develop due to repeated thermal stress and gradually expand, eventually failing in the form of flaking.

[0003] To improve thermal shock resistance and spalling performance, existing technologies typically employ methods such as introducing toughening agents like zirconium oxide, optimizing particle size distribution, or adding pre-synthesized spinel powder. However, these methods still face challenges in practical applications, including uneven distribution of the toughening phase and weak bonding between the aggregate and matrix interfaces. This leads to preferential cracking along the interface during thermal cycling, resulting in limited spalling resistance. Therefore, how to construct a firmly bonded functional interface layer on the aggregate surface, achieve highly uniform in-situ generation of the toughening phase within the matrix, and simultaneously avoid damage to the green body during the drying process has become a critical technical challenge to be addressed in improving the spalling resistance of magnesium aluminate spinel bricks. Summary of the Invention

[0004] To achieve the above objectives, the present invention provides a process for preparing magnesium-aluminum spinel bricks with improved anti-stripping properties.

[0005] A process for preparing magnesium-aluminate spinel bricks with improved anti-stripping properties includes the following steps: S1: Mix fused magnesia particles and magnesium-rich spinel particles, add them to modified silica sol containing nano-zirconia dispersion, stir under vacuum and perform ultrasonic dispersion treatment, and then let stand to solidify to obtain pre-coated aggregate. S2: Alumina micro powder, monoclinic zirconium oxide micro powder and lightly calcined magnesium powder are mixed and wet ball-milled with polyethylene glycol aqueous solution as dispersion medium, followed by spray drying to obtain composite binder powder; S3: Dry mix the pre-coated aggregate obtained in S1 with the composite binder powder obtained in S2 to obtain a premix; S4: Add a temporary binder aqueous solution to the premix obtained in S3 and knead to obtain mud; S5: Press the mud obtained in S4 into shape to obtain brick blanks; S6: Microwave dry the brick blanks obtained in S5 to obtain dry blanks; S7: The dry blank obtained in S6 is fired at high temperature and then cooled in the furnace to obtain magnesium aluminum spinel brick with improved anti-stripping properties.

[0006] Optionally, S1 includes: S11: Heat a silica sol solution with a solid content of 25%-35% to 40-55℃, and add nano-zirconia dispersion dropwise under continuous stirring. The mass ratio of silica sol solution to nano-zirconia dispersion is 100:5-12. After the addition is complete, continue stirring for 20-40 minutes to obtain a mixture. S12: Add an ammonia solution with a concentration of 0.5-1.5 mol / L to the mixture obtained in S11 to adjust the pH value of the mixture to 8.5-10.0. Stir continuously during the pH adjustment process. After the pH value is adjusted to the desired level, continue stirring for 15-25 minutes. Then let it stand at room temperature for 2-4 hours to mature and obtain the modified silica sol.

[0007] Optionally, S1 further includes: S13: Place fused magnesia particles with a particle size of 3-5mm and magnesium-rich spinel particles with a particle size of 1-3mm in a vacuum mixing tank at a mass ratio of 6:4. Evacuate the tank to a vacuum degree of -0.08--0.06MPa and mix for 8-12 minutes at a stirring speed of 60-100r / min to obtain mixed aggregate. S14: Under the conditions of maintaining the vacuum and stirring in S13, add the modified silica sol obtained in S12 to the mixed aggregate obtained in S13 by atomized spraying. The amount of modified silica sol added is 3%-5% of the mass of the mixed aggregate. After spraying, continue stirring for 15-20 minutes. S15: Stop stirring, release the vacuum to normal pressure, and place the mixed aggregate treated in S14 into an ultrasonic dispersion device at an ultrasonic frequency of 25-40kHz and a power density of 0.3-0.6W / cm³. 2 Process for 10-15 minutes under the specified conditions; S16: The mixed aggregate treated with S15 is left to stand and cure for 6-10 hours in an environment with a temperature of 25-35℃ and a relative humidity of 60%-75% to obtain pre-coated aggregate.

[0008] Optionally, S2 specifically includes: S21: Add 55%-65% alumina micro powder, 12%-18% monoclinic zirconium micro powder and 17%-33% lightly calcined magnesia powder to a mixing tank according to the mass percentage, and dry mix for 10-20 minutes to obtain a mixed powder. S22: Add the mixed powder obtained in S21 to a polyethylene glycol aqueous solution with a mass concentration of 0.5%-1.0% to prepare a slurry with a solid content of 40%-55%. Put the slurry into a ball mill, use zirconia balls as the grinding medium, and the ball-to-powder mass ratio is 3-5:1. Ball mill at a speed of 300-400 r / min for 4-8 hours. S23: The slurry after ball milling of S22 is spray-dried at an inlet air temperature of 180-220℃ and an outlet air temperature of 80-100℃ to obtain a composite binder powder with a median particle size D50≤2μm.

[0009] Optionally, S3 specifically includes: S31: Weigh the pre-coated aggregate obtained in S1 and the composite binder powder obtained in S2 at a mass ratio of 7:3. First, put the pre-coated aggregate into the mixer, and then add the composite binder powder accounting for 50% of the total mass of the composite binder powder. Dry mix at a speed of 40-60 r / min for 3-5 minutes. S32: Add all remaining composite binder powder into the mixer and continue to dry mix at a speed of 40-60 r / min for 5-8 minutes to obtain the premix.

[0010] Optionally, S4 specifically includes: S41: Add polyvinyl alcohol powder to deionized water to prepare a polyvinyl alcohol aqueous solution with a mass concentration of 2%-4%, which is used as a temporary binder aqueous solution; S42: Put the premix obtained in S3 into a wet mill, dry mill for 2-4 minutes, then add 3%-5% of a temporary binder aqueous solution of the total mass of the premix, and wet mill for 10-15 minutes under the conditions of mill roller pressure of 0.4-0.8MPa and mill disc speed of 20-30r / min to obtain mud.

[0011] Optionally, S5 specifically includes: S51: Weigh the clay obtained in S4 and put it into the brick mold. The amount of clay put into the mold is 55%-65% of the mold volume. S52: Place the brick mold containing the mud into the hydraulic press and pre-press it with a pressure of 20-30MPa for 3-5 minutes to remove residual gas from the mud. S53: Increase the pressure to 100-120MPa, hold the pressure for 8-12 minutes, and then depressurize at a rate of 2-4MPa / s; S54: Remove the brick blank from the mold and let it stand at room temperature for 4-6 hours to obtain the brick blank.

[0012] Optionally, S6 specifically includes: S61: Place the brick blanks obtained in S5 into a microwave drying device. The spacing between the brick blanks is 30-50mm, and the spacing between the brick blanks and the inner wall of the microwave drying device is 50-80mm. S62: Set the microwave frequency to 2450MHz, the microwave power density to 0.5-1.0W / g, the drying temperature to 60-80℃, and the drying time to 30-60 minutes; S63: Detect the residual moisture of the brick blank. If the residual moisture is less than ≤0.5%, increase the microwave power density in increments of 0.1-0.2W / g, and continue drying for 5-10 minutes after each increase until the residual moisture is ≤0.5%, thus obtaining a dry brick blank.

[0013] Optionally, S7 specifically includes: S71: Load the dry bricks obtained in S6 into a high-temperature kiln. The bricks are stacked in 3-5 layers with a 30-50mm interval between layers. S72: Heat from room temperature to 1100-1200℃ at a heating rate of 3-5℃ / min, and hold for 2-3 hours; S73: Continue heating at a rate of 2-3℃ / min to 1600-1650℃, and hold for 4-6 hours; S74: Cool down to 800-900℃ at a cooling rate of 5-8℃ / min, hold for 1-2 hours, and then cool down to 300-400℃ at a cooling rate of 2-3℃ / min. S75: Turn off the heating power and allow the furnace to cool naturally to room temperature. The resulting magnesium aluminum spinel bricks have improved anti-stripping properties.

[0014] Optionally, the magnesium-aluminate spinel bricks are used in the firing zone, transition zone, or ladle lining of a cement rotary kiln, with a service temperature of 1400-1600℃.

[0015] The beneficial effects of this invention are: This invention employs a modified silica sol containing nano-zirconia dispersion to pre-coat aggregates using vacuum ultrasonic assistance, forming a firmly bonded functional coating on the aggregate surface. During firing, this coating reacts in situ with the matrix components to generate a transition interface layer containing magnesium zirconate seeds, effectively enhancing the bonding strength between the aggregate and the matrix. Simultaneously, it acts as a thermal stress buffer, fundamentally inhibiting the initiation and propagation of interface cracks. Furthermore, microwave drying ensures uniform heating of the brick blank both internally and externally, with a small moisture gradient, eliminating the drying cracking defects easily caused by traditional hot air drying. Attached Figure Description

[0016] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only for this invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0017] Figure 1 This is a schematic diagram of the process flow for preparing magnesium-aluminate spinel bricks according to an embodiment of the present invention. Detailed Implementation

[0018] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. It should also be noted that, to make the embodiments more comprehensive, the following embodiments are the best and preferred embodiments, and those skilled in the art can use other alternative methods to implement some well-known technologies; moreover, the accompanying drawings are only for more specific description of the embodiments and are not intended to specifically limit the present invention.

[0019] It should be noted that the use of terms such as "an embodiment," "an embodiment," "an exemplary embodiment," and "some embodiments" in the specification indicates that the described embodiment may include a specific feature, structure, or characteristic, but not every embodiment necessarily includes that specific feature, structure, or characteristic. Furthermore, when a specific feature, structure, or characteristic is described in connection with an embodiment, implementing such a feature, structure, or characteristic in conjunction with other embodiments (whether explicitly described or not) should be within the knowledge of those skilled in the art.

[0020] Generally, terms can be understood at least partly from their use in context. For example, depending at least partly on the context, the term "one or more" as used herein can be used to describe any feature, structure, or characteristic in a singular sense, or a combination of features, structures, or characteristics in a plural sense. Additionally, the term "based on" can be understood not necessarily to convey an exclusive set of factors, but rather, alternatively, depending at least partly on the context, to allow for the presence of other factors that are not necessarily explicitly described.

[0021] Example 1

[0022] like Figure 1 As shown, a process for preparing magnesium-aluminum spinel bricks with improved anti-stripping properties includes the following steps: S1: Mix fused magnesia particles and magnesium-rich spinel particles, add them to modified silica sol containing nano-zirconia dispersion, stir under vacuum and perform ultrasonic dispersion treatment, and then let stand to solidify to obtain pre-coated aggregate. S2: Alumina micro powder, monoclinic zirconium oxide micro powder and lightly calcined magnesium powder are mixed and wet ball-milled with polyethylene glycol aqueous solution as dispersion medium, followed by spray drying to obtain composite binder powder; S3: Dry mix the pre-coated aggregate obtained in S1 with the composite binder powder obtained in S2 to obtain a premix; S4: Add a temporary binder aqueous solution to the premix obtained in S3 and knead to obtain mud; S5: Press the mud obtained in S4 into shape to obtain brick blanks; S6: Microwave dry the brick blanks obtained in S5 to obtain dry blanks; S7: The dry blank obtained in S6 is fired at high temperature and then cooled in the furnace to obtain magnesium aluminum spinel brick with improved anti-stripping properties.

[0023] S1: Heat a silica sol solution with a solid content of 30% to 47°C, and add nano-zirconia dispersion dropwise under continuous stirring. The mass ratio of silica sol solution to nano-zirconia dispersion is 100:8.5. After the addition is complete, continue stirring for 30 minutes to obtain a mixture. Then, add ammonia solution with a concentration of 1.0 mol / L dropwise to the mixture to adjust the pH value of the mixture to 9.2. Continue stirring during the adjustment process. After the pH value is reached, continue stirring for 20 minutes and let it stand at room temperature for 3 hours to mature, thus obtaining modified silica sol. Subsequently, fused magnesia particles with a particle size of 4 mm and magnesium-rich spinel particles with a particle size of 2 mm were placed in a vacuum mixing tank at a mass ratio of 6:4. The tank was evacuated to a vacuum level of -0.07 MPa and mixed for 10 minutes at a stirring speed of 80 r / min to obtain a mixed aggregate. While maintaining vacuum and stirring, modified silica sol was added to the mixed aggregate via atomized spray, at a concentration of 4% of the aggregate mass. After spraying, stirring continued for 17 minutes. Then, stirring was stopped and the vacuum was released to atmospheric pressure. The treated mixed aggregate was placed in an ultrasonic dispersion device at an ultrasonic frequency of 32 kHz and a power density of 0.45 W / cm³. 2 The mixture was treated under the following conditions for 12 minutes; finally, the ultrasonically treated aggregate was placed in an environment with a temperature of 30℃ and a relative humidity of 68% and allowed to stand and cure for 8 hours to obtain pre-coated aggregate.

[0024] S2: 60% alumina micro powder, 15% monoclinic zirconia micro powder and 25% lightly calcined magnesia powder were added to a mixing tank and dry-mixed for 15 minutes to obtain a mixed powder. The mixed powder was added to a 0.8% polyethylene glycol aqueous solution to prepare a slurry with a solid content of 48%, and then fed into a ball mill. Zirconia balls were used as the grinding medium, and the ball-to-powder mass ratio was 4:1. The mixture was ball-milled for 6 hours at a speed of 350 r / min. The ball-milled slurry was spray-dried at an inlet air temperature of 200℃ and an outlet air temperature of 90℃ to obtain a composite binder powder with a median particle size D50 of 1.6 μm.

[0025] S3: Weigh the pre-coated aggregate and composite binder powder at a mass ratio of 7:3. First, put the pre-coated aggregate into the mixer, then add 50% of the total mass of the composite binder powder and dry mix at 50 r / min for 4 minutes. Then, put the remaining 50% of the composite binder powder into the mixer and continue to dry mix at 50 r / min for 6 minutes to obtain the premix.

[0026] S4: Add polyvinyl alcohol powder to deionized water to prepare a 3% polyvinyl alcohol aqueous solution as a temporary binder aqueous solution; put the premix into a wet mill, dry mill for 3 minutes, then add 4% of the total mass of the premix in the temporary binder aqueous solution, and wet mill for 12 minutes under the conditions of mill roller pressure of 0.6MPa and mill disc speed of 25r / min to obtain mud.

[0027] S5: Weigh the clay and fill it into the brick mold, filling it to 60% of the mold volume; place the brick mold containing the clay in a hydraulic press and pre-press it at 25MPa for 4 minutes to remove residual gas from the clay; then increase the pressure to 110MPa and hold it for 10 minutes, then depressurize at a rate of 3MPa / s; demold the brick and place it at room temperature for 5 hours to obtain the brick blank.

[0028] S6: Place the brick blanks in a microwave drying device, with a spacing of 40mm between adjacent brick blanks and a spacing of 65mm between the brick blanks and the inner wall of the microwave drying device; set the microwave frequency to 2450MHz, the microwave power density to 0.8W / g, the drying temperature to 70℃, and the drying time to 45 minutes; after drying, the residual moisture content of the brick blanks is detected to be 0.42%, which meets the requirement of residual moisture ≤0.5%, therefore the microwave power density is no longer increased, and the dried brick blanks are obtained. In this embodiment, if the residual moisture content does not meet the standard, the microwave power density is increased in increments of 0.15W / g, and drying continues for 7 minutes after each increase until the residual moisture content is ≤0.5%.

[0029] S7: Load the dry bricks into a high-temperature kiln, stacking the bricks in 4 layers with a 40mm interval between layers; raise the temperature from room temperature to 1150℃ at a rate of 4℃ / min and hold for 2.5 hours; then raise the temperature to 1625℃ at a rate of 2.5℃ / min and hold for 5 hours; then lower the temperature to 850℃ at a rate of 6.5℃ / min and hold for 1.5 hours; then lower the temperature to 350℃ at a rate of 2.5℃ / min; finally turn off the heating power and allow the kiln to cool naturally to room temperature, yielding magnesium-aluminate spinel bricks with improved anti-stripping properties.

[0030] Example 2

[0031] S1: Heat a silica sol solution with a solid content of 25% to 40°C, and add nano-zirconia dispersion dropwise under continuous stirring. The mass ratio of silica sol solution to nano-zirconia dispersion is 100:5. After the addition is complete, continue stirring for 20 minutes to obtain a mixture. Then, add ammonia solution with a concentration of 0.5 mol / L dropwise to the mixture to adjust the pH value of the mixture to 8.5. Continue stirring during the adjustment process. After the pH value is reached, continue stirring for 15 minutes and let it stand at room temperature for 2 hours to mature, thus obtaining modified silica sol. Subsequently, fused magnesia particles with a particle size of 3 mm and magnesium-rich spinel particles with a particle size of 1 mm were placed in a vacuum mixing tank at a mass ratio of 6:4. The tank was evacuated to a vacuum level of -0.06 MPa and mixed for 8 minutes at a stirring speed of 60 r / min to obtain a mixed aggregate. While maintaining vacuum and stirring, modified silica sol was added to the mixed aggregate via atomized spraying at a concentration of 3% of the aggregate mass. After spraying, stirring was continued for 15 minutes. Stirring was then stopped, and the vacuum was released to atmospheric pressure. The treated mixed aggregate was then placed in an ultrasonic dispersion device at an ultrasonic frequency of 25 kHz and a power density of 0.3 W / cm³. 2 The mixture was treated under the following conditions for 10 minutes; finally, the ultrasonically treated aggregate was placed in an environment with a temperature of 25°C and a relative humidity of 60% and allowed to stand for 6 hours to cure, thus obtaining pre-coated aggregate.

[0032] S2: 55% alumina micro powder, 12% monoclinic zirconia micro powder and 33% lightly calcined magnesia powder were added to a mixing tank and dry-mixed for 10 minutes to obtain a mixed powder. The mixed powder was added to a 0.5% polyethylene glycol aqueous solution to prepare a slurry with a solid content of 40%, and then fed into a ball mill. Zirconia balls were used as the grinding medium, and the ball-to-powder mass ratio was 3:1. The mixture was ball-milled for 4 hours at a speed of 300 r / min. The ball-milled slurry was spray-dried at an inlet air temperature of 180℃ and an outlet air temperature of 80℃ to obtain a composite binder powder with a median particle size D50 of 1.9 μm.

[0033] S3: Weigh the pre-coated aggregate and composite binder powder at a mass ratio of 7:3. First, put the pre-coated aggregate into the mixer, then add 50% of the total mass of the composite binder powder and dry mix at 40 r / min for 3 minutes. Then, put the remaining 50% of the composite binder powder into the mixer and continue to dry mix at 40 r / min for 5 minutes to obtain the premix.

[0034] S4: Add polyvinyl alcohol powder to deionized water to prepare a 2% polyvinyl alcohol aqueous solution as a temporary binder aqueous solution; put the premix into a wet mill, dry mill for 2 minutes, then add 3% of the total mass of the premix in the temporary binder aqueous solution, and wet mill for 10 minutes under the conditions of mill roller pressure of 0.4MPa and mill disc speed of 20r / min to obtain mud.

[0035] S5: Weigh the clay and fill it into the brick mold, filling it to 55% of the mold volume; place the brick mold containing the clay in a hydraulic press and pre-press it at 20MPa for 3 minutes to remove residual gas from the clay; then increase the pressure to 100MPa and hold it for 8 minutes, and then depressurize it at a rate of 2MPa / s; demold the brick and place it at room temperature for 4 hours to obtain the brick blank.

[0036] S6: Place the brick blanks in a microwave drying device with a spacing of 30mm between adjacent brick blanks and a spacing of 50mm between the brick blanks and the inner wall of the microwave drying device; set the microwave frequency to 2450MHz, the microwave power density to 0.5W / g, the drying temperature to 60℃, and the drying time to 30 minutes; after the first drying, the residual moisture content of the brick blanks was 0.62%, which did not meet the requirement of ≤0.5% residual moisture. Therefore, the microwave power density was increased from 0.1W / g to 0.6W / g, and drying was continued for 5 minutes. The residual moisture content was then checked again and found to be 0.48%, thus obtaining the dried brick blanks.

[0037] S7: Load the dry bricks into a high-temperature kiln, stacking the bricks in 3 layers with a 30mm interval between layers; raise the temperature from room temperature to 1100℃ at a rate of 3℃ / min and hold for 2 hours; then raise the temperature to 1600℃ at a rate of 2℃ / min and hold for 4 hours; then lower the temperature to 800℃ at a rate of 5℃ / min and hold for 1 hour; then lower the temperature to 300℃ at a rate of 2℃ / min; finally turn off the heating power and allow the kiln to cool naturally to room temperature, yielding magnesium-aluminate spinel bricks with improved anti-stripping properties.

[0038] Example 3

[0039] S1: Heat a silica sol solution with a solid content of 35% to 55°C, and add nano-zirconia dispersion dropwise under continuous stirring. The mass ratio of silica sol solution to nano-zirconia dispersion is 100:12. After the addition is complete, continue stirring for 40 minutes to obtain a mixture. Then, add ammonia solution with a concentration of 1.5 mol / L dropwise to the mixture to adjust the pH value of the mixture to 10.0. Continue stirring during the adjustment process. After the pH value is reached, continue stirring for 25 minutes and let it stand at room temperature for 4 hours to mature, thus obtaining modified silica sol. Then, fused magnesia particles with a particle size of 5 mm and magnesium-rich spinel particles with a particle size of 3 mm were placed in a vacuum mixing tank at a mass ratio of 6:4. The tank was evacuated to a vacuum degree of -0.08 MPa and stirred for 12 minutes at a stirring speed of 100 r / min to obtain a mixed aggregate. While maintaining the vacuum and stirring conditions, modified silica sol was added to the mixed aggregate by atomization spraying. The amount of modified silica sol added was 5% of the mass of the mixed aggregate. After spraying, stirring was continued for 20 minutes. Then, stirring was stopped and the vacuum was released to atmospheric pressure. The treated mixed aggregate was placed in an ultrasonic dispersion device and subjected to ultrasonic dispersion at a frequency of 40 kHz and a power density of 0.6 W / cm³. 2 The mixture was treated under the following conditions for 15 minutes; finally, the ultrasonically treated aggregate was placed in an environment with a temperature of 35℃ and a relative humidity of 75% and allowed to stand and cure for 10 hours to obtain pre-coated aggregate.

[0040] S2: 65% alumina micro powder, 18% monoclinic zirconia micro powder and 17% lightly calcined magnesia powder were added to a mixing tank and dry-mixed for 20 minutes to obtain a mixed powder. The mixed powder was added to a 1.0% (w / w) polyethylene glycol aqueous solution to prepare a slurry with a solid content of 55%, and then fed into a ball mill. Zirconia balls were used as the grinding medium, and the ball-to-particle mass ratio was 5:1. The mixture was ball-milled for 8 hours at a speed of 400 r / min. The ball-milled slurry was spray-dried at an inlet air temperature of 220℃ and an outlet air temperature of 100℃ to obtain a composite binder powder with a median particle size D50 of 1.2 μm.

[0041] S3: Weigh the pre-coated aggregate and composite binder powder at a mass ratio of 7:3. First, put the pre-coated aggregate into the mixer, then add 50% of the total mass of the composite binder powder and dry mix at 60 r / min for 5 minutes. Then, put the remaining 50% of the composite binder powder into the mixer and continue to dry mix at 60 r / min for 8 minutes to obtain the premix.

[0042] S4: Add polyvinyl alcohol powder to deionized water to prepare a 4% polyvinyl alcohol aqueous solution as a temporary binder aqueous solution; put the premix into a wet mill, dry mill for 4 minutes, then add 5% of the total mass of the premix of the temporary binder aqueous solution, and wet mill for 15 minutes under the conditions of mill roller pressure of 0.8MPa and mill disc speed of 30r / min to obtain mud.

[0043] S5: Weigh the clay and fill it into the brick mold, filling it to 65% of the mold volume; place the brick mold containing the clay in a hydraulic press and pre-press it at 30MPa for 5 minutes to remove residual gas from the clay; then increase the pressure to 120MPa and hold it for 12 minutes, then depressurize at a rate of 4MPa / s; demold the brick and place it at room temperature for 6 hours to obtain the brick blank.

[0044] S6: Place the brick blanks in a microwave drying device, with a spacing of 50mm between adjacent brick blanks and 80mm between the brick blanks and the inner wall of the microwave drying device; set the microwave frequency to 2450MHz, the microwave power density to 1.0W / g, the drying temperature to 80℃, and the drying time to 60 minutes; after drying, the residual moisture content of the brick blanks is detected to be 0.36%, which meets the requirement of residual moisture ≤0.5%, therefore the microwave power density is no longer increased, and the dried brick blanks are obtained. In this embodiment, if the residual moisture content does not meet the standard, the microwave power density is increased in increments of 0.2W / g, and drying continues for 10 minutes after each increase until the residual moisture content is ≤0.5%.

[0045] S7: Load the dry bricks into a high-temperature kiln, stacking them in 5 layers with a 50mm interval between layers; raise the temperature from room temperature to 1200℃ at a rate of 5℃ / min and hold for 3 hours; then raise the temperature to 1650℃ at a rate of 3℃ / min and hold for 6 hours; then lower the temperature to 900℃ at a rate of 8℃ / min and hold for 2 hours; then lower the temperature to 400℃ at a rate of 3℃ / min; finally turn off the heating power and allow the kiln to cool naturally to room temperature, yielding magnesium-aluminate spinel bricks with improved anti-stripping properties.

[0046] Comparative Example 1 This comparative example uses conventional dry batching, wet milling and mixing, semi-dry pressing, hot air drying, and high-temperature calcination processes. It does not involve nano-zirconia dispersion-modified silica sol coating treatment, nor does it employ wet ball milling or spray drying with composite binders, nor microwave drying. Specifically: S1: Weigh 70 parts of fused magnesia particles, 20 parts of sintered magnesium aluminum spinel particles, 5 parts of alumina micro powder and 5 parts of lightly calcined magnesia powder; put the above raw materials into a forced mixer and dry mix at 60 r / min for 15 minutes to obtain a conventional mixture.

[0047] S2: Add 4% by mass of calcium lignosulfonate aqueous solution to the conventional mixture obtained in S1, wherein the mass concentration of the calcium lignosulfonate aqueous solution is 3%; then feed the material into a wet mill and wet mill for 20 minutes at a mill speed of 25 r / min and a mill pressure of 0.5 MPa to obtain conventional mud.

[0048] S3: The conventional clay obtained in S2 is loaded into the brick mold and pressed into shape using a hydraulic press at a pressure of 100MPa. After holding the pressure for 8 minutes, the brick is demolded to obtain a conventional brick blank. The conventional brick blank is placed in a hot air drying kiln and dried at 110℃ for 24 hours. After drying, the residual moisture of the brick blank is controlled to be 0.8%.

[0049] S4: The dried conventional brick blanks are loaded into a tunnel kiln and heated to 1650℃ at 4℃ / min under a weak oxidizing atmosphere, and held for 5 hours. After the holding period, the temperature is reduced to 800℃ at 5℃ / min, and then cooled to room temperature with the furnace. Conventional magnesium aluminum spinel bricks are obtained after being taken out of the furnace.

[0050] Table 1 Comparison of Finished Product Performance Parameters

[0051] As shown in Table 1 above, Example 1 exhibits the best overall performance, with a bulk density of 3.18 g·cm³. -3 The apparent porosity decreased to 12.6%, indicating a denser structure after sintering. The room temperature compressive strength and flexural strength at 1400℃ reached 92.5 MPa and 18.6 MPa respectively, both significantly higher than Comparative Example 1. This demonstrates that the synergistic effect of pre-coated aggregate and composite binder powder improves the bond strength between the aggregate and the matrix. Furthermore, Example 1 exhibited 24 thermal shock cycles under water cooling at 1100℃, with a strength retention rate of 82.4% and a spalling mass loss rate of only 1.8%, significantly better than Comparative Example 1's 12 cycles, 61.8%, and 5.6%, respectively. This indicates that the present invention, through coating the aggregate with nano-zirconia-modified silica sol and combining it with monoclinic zirconia micropowder, alumina micropowder, and lightly calcined magnesia powder to form a refined composite bonding system, can alleviate thermal stress concentration during high-temperature service, reduce the risk of surface cracking and spalling of the brick, and thus effectively improve the spalling resistance and service stability of magnesia-alumina spinel bricks.

[0052] Table 2 Comparison of performance parameters in other directions

[0053] As shown in Table 2 above, Example 1 outperforms Examples 2, 3, and Comparative Example 1 in terms of load softening start temperature, reheating linear change rate, slag erosion resistance depth, slag penetration resistance depth, and high-temperature creep rate. Specifically, Example 1's load softening start temperature reaches 1715℃, higher than Comparative Example 1's 1635℃, indicating better high-temperature load-bearing stability. The reheating linear change rate under 1600℃×3h conditions is only +0.08%, indicating smaller dimensional changes in the brick at high temperatures, making it less prone to structural stress due to volume fluctuations during service. Furthermore, Example 1's slag erosion resistance depth and slag penetration resistance depth are 2.1mm and 3.4mm respectively, significantly lower than Comparative Example 1's 5.8mm and 7.6mm, demonstrating that the invention, through pre-coated aggregate and refined composite binder powder, forms a more continuous and denser matrix bonding structure, reducing the degree of slag penetration into the brick. Example 1 has a thermal conductivity of 3.25 W·m at 1000℃. -1 ·K -1 This is lower than the 4.35 W·m of Comparative Example 1. -1 ·K -1 This reduces the transmission of localized thermal shock; its high-temperature creep rate is only 0.18%, and the surface crack width after service simulation is only 0.06 mm, indicating that the brick can still maintain good structural integrity under high-temperature load and temperature fluctuation conditions.

[0054] In summary, Example 1 achieved a balance between aggregate coating degree, binder refinement degree, molding density and firing reaction degree through intermediate parameter conditions. This resulted in magnesium aluminum spinel bricks not only having better anti-stripping properties, but also performing better in terms of slag erosion resistance, volume stability, high temperature load-bearing capacity and post-service crack control. As a result, they are better suited for high-temperature erosion and thermal shock alternating environments such as the firing zone, transition zone or steel ladle lining of cement rotary kilns.

[0055] This invention encompasses any substitutions, modifications, equivalent methods, and solutions made within the spirit and scope of this invention. To provide the public with a thorough understanding of this invention, specific details are described in detail in the following preferred embodiments; however, those skilled in the art will fully understand the invention even without these details. Furthermore, to avoid unnecessary misunderstanding of the essence of this invention, well-known methods, processes, procedures, components, and circuits are not described in detail.

[0056] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A process for preparing magnesium-aluminate spinel bricks with improved anti-stripping properties, characterized in that, Includes the following steps: S1: Mix fused magnesia particles and magnesium-rich spinel particles, add them to modified silica sol containing nano-zirconia dispersion, stir under vacuum and perform ultrasonic dispersion treatment, and then let stand to solidify to obtain pre-coated aggregate. S2: Alumina micro powder, monoclinic zirconium oxide micro powder and lightly calcined magnesium powder are mixed and wet ball-milled with polyethylene glycol aqueous solution as dispersion medium, followed by spray drying to obtain composite binder powder; S3: Dry mix the pre-coated aggregate obtained in S1 with the composite binder powder obtained in S2 to obtain a premix; S4: Add a temporary binder aqueous solution to the premix obtained in S3 and knead to obtain mud; S5: Press the mud obtained in S4 into shape to obtain brick blanks; S6: Microwave dry the brick blanks obtained in S5 to obtain dry blanks; S7: The dry blank obtained in S6 is fired at high temperature and then cooled in the furnace to obtain magnesium aluminum spinel brick with improved anti-stripping properties.

2. The process for preparing magnesium-aluminate spinel bricks with improved anti-stripping properties according to claim 1, characterized in that, S1 includes: S11: Heat a silica sol solution with a solid content of 25%-35% to 40-55℃, and add nano-zirconia dispersion dropwise under continuous stirring. The mass ratio of silica sol solution to nano-zirconia dispersion is 100:5-12. After the addition is complete, continue stirring for 20-40 minutes to obtain a mixture. S12: Add an ammonia solution with a concentration of 0.5-1.5 mol / L to the mixture obtained in S11 to adjust the pH value of the mixture to 8.5-10.

0. Stir continuously during the pH adjustment process. After the pH value is adjusted to the desired level, continue stirring for 15-25 minutes. Then let it stand at room temperature for 2-4 hours to mature and obtain the modified silica sol.

3. The process for preparing magnesium-aluminate spinel bricks with improved anti-stripping properties according to claim 2, characterized in that, S1 further includes: S13: Place fused magnesia particles with a particle size of 3-5mm and magnesium-rich spinel particles with a particle size of 1-3mm in a vacuum mixing tank at a mass ratio of 6:

4. Evacuate the tank to a vacuum degree of -0.08--0.06MPa and mix for 8-12 minutes at a stirring speed of 60-100r / min to obtain mixed aggregate. S14: Under the conditions of maintaining the vacuum and stirring in S13, add the modified silica sol obtained in S12 to the mixed aggregate obtained in S13 by atomized spraying. The amount of modified silica sol added is 3%-5% of the mass of the mixed aggregate. After spraying, continue stirring for 15-20 minutes. S15: Stop stirring, release the vacuum to normal pressure, and place the mixed aggregate treated in S14 into an ultrasonic dispersion device at an ultrasonic frequency of 25-40kHz and a power density of 0.3-0.6W / cm³. 2 Process for 10-15 minutes under the specified conditions; S16: The mixed aggregate treated with S15 is left to stand and cure for 6-10 hours in an environment with a temperature of 25-35℃ and a relative humidity of 60%-75% to obtain pre-coated aggregate.

4. The process for preparing magnesium-aluminate spinel bricks with improved anti-stripping properties according to claim 1, characterized in that, S2 specifically includes: S21: Add 55%-65% alumina micro powder, 12%-18% monoclinic zirconium micro powder and 17%-33% lightly calcined magnesia powder to a mixing tank according to the mass percentage, and dry mix for 10-20 minutes to obtain a mixed powder. S22: Add the mixed powder obtained in S21 to a polyethylene glycol aqueous solution with a mass concentration of 0.5%-1.0% to prepare a slurry with a solid content of 40%-55%. Put the slurry into a ball mill, use zirconia balls as the grinding medium, and the ball-to-powder mass ratio is 3-5:

1. Ball mill at a speed of 300-400 r / min for 4-8 hours. S23: The slurry after ball milling of S22 is spray-dried at an inlet air temperature of 180-220℃ and an outlet air temperature of 80-100℃ to obtain a composite binder powder with a median particle size D50≤2μm.

5. The process for preparing magnesium-aluminate spinel bricks with improved anti-stripping properties according to claim 1, characterized in that, S3 specifically includes: S31: Weigh the pre-coated aggregate obtained in S1 and the composite binder powder obtained in S2 at a mass ratio of 7:

3. First, put the pre-coated aggregate into the mixer, and then add the composite binder powder accounting for 50% of the total mass of the composite binder powder. Dry mix at a speed of 40-60 r / min for 3-5 minutes. S32: Add all remaining composite binder powder into the mixer and continue to dry mix at a speed of 40-60 r / min for 5-8 minutes to obtain the premix.

6. The process for preparing magnesium-aluminate spinel bricks with improved anti-stripping properties according to claim 1, characterized in that, S4 specifically includes: S41: Add polyvinyl alcohol powder to deionized water to prepare a polyvinyl alcohol aqueous solution with a mass concentration of 2%-4%, which is used as a temporary binder aqueous solution; S42: Put the premix obtained in S3 into a wet mill, dry mill for 2-4 minutes, then add 3%-5% of a temporary binder aqueous solution of the total mass of the premix, and wet mill for 10-15 minutes under the conditions of mill roller pressure of 0.4-0.8MPa and mill disc speed of 20-30r / min to obtain mud.

7. The process for preparing magnesium-aluminate spinel bricks with improved anti-stripping properties according to claim 1, characterized in that, S5 specifically includes: S51: Weigh the clay obtained in S4 and put it into the brick mold. The amount of clay put into the mold is 55%-65% of the mold volume. S52: Place the brick mold containing the mud into the hydraulic press and pre-press it with a pressure of 20-30MPa for 3-5 minutes to remove residual gas from the mud. S53: Increase the pressure to 100-120MPa, hold the pressure for 8-12 minutes, and then depressurize at a rate of 2-4MPa / s; S54: Remove the brick blank from the mold and let it stand at room temperature for 4-6 hours to obtain the brick blank.

8. The process for preparing magnesium-aluminate spinel bricks with improved anti-stripping properties according to claim 1, characterized in that, S6 specifically includes: S61: Place the brick blanks obtained in S5 into a microwave drying device. The spacing between the brick blanks is 30-50mm, and the spacing between the brick blanks and the inner wall of the microwave drying device is 50-80mm. S62: Set the microwave frequency to 2450MHz, the microwave power density to 0.5-1.0W / g, the drying temperature to 60-80℃, and the drying time to 30-60 minutes; S63: Detect the residual moisture of the brick blank. If the residual moisture is less than ≤0.5%, increase the microwave power density in increments of 0.1-0.2W / g, and continue drying for 5-10 minutes after each increase until the residual moisture is ≤0.5%, thus obtaining a dry brick blank.

9. The process for preparing magnesium-aluminate spinel bricks with improved anti-stripping properties according to claim 1, characterized in that, Specifically, S7 includes: S71: Load the dry bricks obtained in S6 into a high-temperature kiln. The bricks are stacked in 3-5 layers with a 30-50mm interval between layers. S72: Heat from room temperature to 1100-1200℃ at a heating rate of 3-5℃ / min, and hold for 2-3 hours; S73: Continue heating at a rate of 2-3℃ / min to 1600-1650℃, and hold for 4-6 hours; S74: Cool down to 800-900℃ at a cooling rate of 5-8℃ / min, hold for 1-2 hours, and then cool down to 300-400℃ at a cooling rate of 2-3℃ / min. S75: Turn off the heating power and allow the furnace to cool naturally to room temperature. The resulting magnesium aluminum spinel bricks have improved anti-stripping properties.

10. The process for preparing magnesium-aluminate spinel bricks with improved anti-stripping properties according to claim 1, characterized in that, The magnesium-aluminate spinel bricks are used in the firing zone, transition zone, or ladle lining of cement rotary kilns, with a service temperature of 1400-1600℃.